ANALISIS PEMILIHAN SUPPLIER BERAS DI TOKO SEMBAKO GABE - Purba, Risdohar; Asmarawati, Citra Indah (Computer Science and Industrial Engineering, 2023)
In the face of increasingly rapid market developments, every company must be able to compete globally. This is a challenge for every company, to be able to compete in providing the best for its consumers. In order to produce products that are in accordance with the wishes of consumers and can increase the competitiveness of companies, it is necessary to pay attention to how to procure products and select the right suppliers. Toko Sembako Gabe is one of the SMEs that does not yet have the right supplier to become a rice supplier. This research aims to assist business owners in determining the right rice supplier at Gabe Grocery Stores. This research uses the Analytical Hierarchy Process (AHP) method. The criteria used in this study are quality, price, delivery, flexible and fast response. Based on the criteria and sub-criteria in supplier selection, supplier 1 is the first priority with a weight of 1.080, supplier 3 is the second choice with a weight of 0.695 and supplier 2 is the last choice with a weight of 0.288. Based on the results of this study, the best supplier to be chosen by Toko Sembako Gabe is supplier 1 (Grosir Tiga Brother)